Pharmacology and Phytochemistry of Oleo-Gum Resin of Commiphora wightii (Guggulu). (26th October 2015) - Sarup, Prerna; Bala, Suman; Kamboj, Sunil
Abstract : Guggulu is an oleo-gum resin which exudes out as a result of injury from the bark of Commiphora wightii (Arnott) Bhandari [syn.   Commiphora mukul (Hook. Ex Stocks) Engl; Balsamodendron mukul (Hook. Ex Stocks); Family, Burseraceae]. It has been used in the Ayurveda since time immemorial for the treatment of variety of disorders such as inflammation, gout, rheumatism, obesity, and disorders of lipids metabolism. It is a mixture of phytoconstituents like volatile oil which contains terpenoidal constituents such as monoterpenoids, sesquiterpenoids, diterpenoids, and triterpenoids; steroids; flavonoids; guggultetrols; lignans; sugars; and amino acids. This review is an effort to compile all the information available on all of its chemical constituents which are responsible for its therapeutic potential. The wild occurrence of this species is restricted mainly to the dry regions of Rajasthan and Gujarat States of India, and the bordering regions of Pakistan. Oleo-gum resin, guggulu, tapped from the stems of this species, is consumed in high volumes by the Indian herbal industries. There has been a decline in its wild population over the last several decades, as a result of habitat loss and degradation, coupled with unregulated harvesting and tapping of oleo-gum resin. This species is consequently assessed as Critically Endangered and enlisted in the IUCN red list of threatened species.